Pengaruh Tone at the Top dan Locus of Control terhadap Perilaku Disfungsional Audit: Studi Eksperimental pada Mahasiswa S1 Akuntansi Universitas Negeri Padang - Destri Andriani; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2022)
The purpose of this study is to analyze the effect of tone at the top and locus of control on dysfunctional audit behavior. is study used a-quasi experimental desaign with 2x2 factorial design. The hypothesis in this study tested by using measures Two way ANOVA. The result of this study indicate that auditors will act dysfunctionally when he knows that tone at the top accepts the dysfunctional audit behavior. Also, the result of this study found that the auditor’s locus of control has an affect on dysfunctional audit behavior. Furthermore, the result of this study found that there is no interaction between tone at the top and locus of control on dysfunctional audit behavior.